Sistema inteligente con visión artificial para el reconocimiento de piezas mecánicas en el Robot NAO - Cadena Castro, Lenin Marcel (2018)
This document details the construction and operation of an intelligent system with artificial vision, this is composed of two algorithms: first it is recognition and identification of mechanical parts through Hu's invariant moments and an artificial neural network in MATLAB software. Second is based on the identification of color patterns through the OpenCV library in Python for robot orientation. It do an intercommunication between MATLAB-Python software through the VSP program (Virtual Serial Port Emulator) between the two programs, exchanging data such as the response of the artificial neural network, the position where the object is located and the information for positioning the robot of the real working environment. The patterns to be discriminated are: screw, pins and terminals that will be classified by the NAO robot as mechanical parts of a production line. An algorithm was developed for the evasion of any obstacle located in the surface of mobility of the android, for this were used the sensors bumpers of the feet, which will be activated that it can surround it and continue with the trajectory, it is important to detail that to obtain A rectilinear movement was performed several methods of correction of position, thus having an optimal functioning of the system.